Asksia AI LOGO

Sia

Question
Math
Posted 9 months ago
given that log3(2)=x, express log8(24) in terms of x
Sign in to unlock the answer
Answer from Sia
Posted 9 months ago
Solution by Steps
step 1
Given that log3(2)=x \log_3(2) = x , we need to express log8(24) \log_8(24) in terms of x x
step 2
We start by expressing log8(24) \log_8(24) using the change of base formula: log8(24)=log(24)log(8) \log_8(24) = \frac{\log(24)}{\log(8)}
step 3
Next, we express log(24) \log(24) and log(8) \log(8) in terms of base 3: log(24)=log(38)=log(3)+log(8) \log(24) = \log(3 \cdot 8) = \log(3) + \log(8) and log(8)=log(23)=3log(2) \log(8) = \log(2^3) = 3 \log(2)
step 4
Substitute log(8) \log(8) and log(24) \log(24) into the change of base formula: log8(24)=log(3)+log(8)3log(2) \log_8(24) = \frac{\log(3) + \log(8)}{3 \log(2)}
step 5
Since log(8)=3log(2) \log(8) = 3 \log(2) , we can rewrite the numerator: log(3)+3log(2) \log(3) + 3 \log(2)
step 6
Substitute log(2)=x \log(2) = x and log(3)=log(2)x \log(3) = \frac{\log(2)}{x} : log8(24)=log(2)x+3log(2)3log(2) \log_8(24) = \frac{\frac{\log(2)}{x} + 3 \log(2)}{3 \log(2)}
step 7
Simplify the expression: log8(24)=log(2)(1x+3)3log(2)=13(1x+3) \log_8(24) = \frac{\log(2) ( \frac{1}{x} + 3 )}{3 \log(2)} = \frac{1}{3} ( \frac{1}{x} + 3 )
step 8
Further simplify: log8(24)=13x+1 \log_8(24) = \frac{1}{3x} + 1
Answer
log8(24)=13x+1 \log_8(24) = \frac{1}{3x} + 1
Key Concept
Change of Base Formula
Explanation
The change of base formula allows us to express logarithms in terms of a different base, which is useful for converting between different logarithmic expressions.

Not the question you are looking for? Ask here!

Enter question by text

Enter question by image

Unlock Smarter Learning with AskSia Super!

Join Super, our all-in-one AI solution that can greatly improve your learning efficiency.

30% higher accuracy than GPT-4o
Entire learning journey support
The most student-friendly features
Study Other Question